2018
DOI: 10.1002/ijch.201700060
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Mesembrine – The Construction of Quaternary Stereocenters by Gold‐Catalyzed Diyne Desymmetrization

Abstract: This review gives an overview on synthetic methodology developed for the synthesis of the naturally occurring alkaloid mesembrine. Its all‐carbon‐substituted quaternary stereocenter has fuelled creativity in the application of ex‐chiral‐pool‐synthesis, chiral auxiliaries, and asymmetric catalysis alike. The gold‐catalyzed desymmetrization of 1,4‐diynes has been demonstrated as a selective method for the enantioselective preparation of methylene pyrrolidines incorporating a quaternary stereocenter. The applicab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…In 1987, the first homogeneous gold-catalyzed addition of nucleophiles to alkynes was realized by the group of Utimoto using sodium tetrachloroaurate dihydrate. , One decade later, Teles et al and Tanaka et al demonstrated the possibility of activating alkynes using gold­(I) complexes. From that point, the field of gold­(I) catalysis started to gain momentum year after year and still today remains one of the most active areas of research in organometallic chemistry. , This comes as a consequence of the ability of gold­(I) complexes to activate π bonds in a very selective manner. Its potential, attributed partially to relativistic effects, is illustrated by the wide molecular complexity that can be built through the gold­(I)-catalyzed cycloisomerization of enynes (Scheme ). …”
Section: Introductionmentioning
confidence: 99%
“…In 1987, the first homogeneous gold-catalyzed addition of nucleophiles to alkynes was realized by the group of Utimoto using sodium tetrachloroaurate dihydrate. , One decade later, Teles et al and Tanaka et al demonstrated the possibility of activating alkynes using gold­(I) complexes. From that point, the field of gold­(I) catalysis started to gain momentum year after year and still today remains one of the most active areas of research in organometallic chemistry. , This comes as a consequence of the ability of gold­(I) complexes to activate π bonds in a very selective manner. Its potential, attributed partially to relativistic effects, is illustrated by the wide molecular complexity that can be built through the gold­(I)-catalyzed cycloisomerization of enynes (Scheme ). …”
Section: Introductionmentioning
confidence: 99%
“…For example, the groups of Nishibayashi, Carreira, and Song have reported elegant propargylation methods to access quaternary carbon stereocenters, respectively. Czekelius and co-workers have developed enantioselective synthesis of alkyne substituted quaternary stereocenter through desymmetrization of diynamides . We are aware of only one example that generates alkyne-substituted all-carbon quaternary stereocenter through metal-catalyzed alkynyl addition.…”
Section: Introductionmentioning
confidence: 99%